Modeling consumer confidence and its role for expectation formation: A horse race - Tae-Seok Jang; Stephen Sacht (Kiel University, Department of Economics, 2017)
The notion of bounded rationality has received a considerable attention in the midst of debate over the usefulness of various macroeconomic models. In this paper we empirically seek to analyze the baseline New-Keynesian model with heterogeneous agents who may adopt various heuristics used to forecast future movements in consumption. Agents could exhibit an optimistic or pessimistic view or act as fundamentalists or chartists when forming expectations on future consumption based on discrete choice. Our empirical results via the Simulated Method of Moment Approach show that consumer confidence in the US is heavily grounded on consumers' emotional state (with respect to optimism and pessimism), while for the Euro Area it is most likely technical in nature (with respect to fundamentalists and chartists). These heuristics lead to an equivalent or even better fit to the data compared to the hybrid version of the baseline New-Keynesian model. We argue that this study could open up new possibilities for estimating bounded rationality models and policy analysis.
Keywords: C53; D83; E12; E32; 330; Bounded Rationality; Consumer Confidence; New-Keynesian Model; Forecast Heuristics; Simulated Method of Moments